2021
DOI: 10.4254/wjh.v13.i1.109
|View full text |Cite
|
Sign up to set email alerts
|

Association of interferon lambda-4 rs12979860 polymorphism with hepatocellular carcinoma in patients with chronic hepatitis C infection

Abstract: BACKGROUND Hepatitis C virus (HCV) infection is a public health concern worldwide. Several factors, including genetic polymorphisms, may be evolved in the progression of HCV infection to liver diseases. Interferon lambdas (IFNLs) modulate the immune response during viral infections. IFNLs induce antiviral activity, interfering in the viral replication by promoting the expression of several genes that regulate immunological functions. The interferon lambda-4 ( IFNL4 ) rs1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…HCC accounts for 80% of all primary liver cancers, and it is ranked as the fifth most common cancer and the third leading cause of cancer death in the world (de Bitencorte et al, 2021). HCC development is very complex with the contribution of several etiological and risk factors, including viral factors (e.g., HCV and hepatitis B virus (HBV)) and nonviral factors (e.g., alcohol and diabetes) (Makarova-Rusher et al, 2016).…”
Section: Hepatitis C Virus (Hcv) Infection Is a Global Health Problem...mentioning
confidence: 99%
See 1 more Smart Citation
“…HCC accounts for 80% of all primary liver cancers, and it is ranked as the fifth most common cancer and the third leading cause of cancer death in the world (de Bitencorte et al, 2021). HCC development is very complex with the contribution of several etiological and risk factors, including viral factors (e.g., HCV and hepatitis B virus (HBV)) and nonviral factors (e.g., alcohol and diabetes) (Makarova-Rusher et al, 2016).…”
Section: Hepatitis C Virus (Hcv) Infection Is a Global Health Problem...mentioning
confidence: 99%
“…Interferon lambda 3 (IFN-λ3) is a proinflammatory cytokine that plays a crucial role in combating HCV by regulating the transcription of interferon-stimulating genes. The IFN-λ3-encoding gene is located on chromosome 19q13 (de Bitencorte et al, 2021). Several studies, including ours, have found that the rs12979860 single nucleotide polymorphism (SNP) present upstream of IFN-λ3 (~3 kb) has high predictive power for clinical (e.g., the progression of hepatic fibrosis) and treatment (e.g., the response to pegylated-IFNα plus ribavirin therapy and DAA therapy) outcomes in the case of HCV infection (El-Awady et al, 2012;Ge et al, 2009;Marwa 2021;Rauch et al, 2010;Tanaka et al, 2009;Thomas et al, 2009).…”
Section: Hepatitis C Virus (Hcv) Infection Is a Global Health Problem...mentioning
confidence: 99%